2021
DOI: 10.1002/lio2.574
|View full text |Cite
|
Sign up to set email alerts
|

Early pediatric Cochlear implantation: An update

Abstract: The criteria and candidacy for pediatric cochlear implantation (CI) has significantly transformed over the past few decades and continues to evolve with technological advancements, and recognition of benefit in more diverse populations. Prolonged auditory deprivation among patients with profound sensorineural hearing loss has been shown to cause widespread degeneration in the central auditory system. Thus, there is increasing evidence advocating for earlier implantation within a critical neuroplastic window. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 88 publications
(135 reference statements)
0
11
0
2
Order By: Relevance
“…Early implantation may alleviate auditory deprivation, improve language development, and attain better vocabulary and linguistic outcomes. [43][44][45][46][47][48] The correlation between speech reception and age at implant for children with CI have been a controversial issue in past decades. [49][50][51][52][53] For example, Dettman et al [48] reported a significant relationship between age of implantation and speech perception.…”
Section: Discussionmentioning
confidence: 99%
“…Early implantation may alleviate auditory deprivation, improve language development, and attain better vocabulary and linguistic outcomes. [43][44][45][46][47][48] The correlation between speech reception and age at implant for children with CI have been a controversial issue in past decades. [49][50][51][52][53] For example, Dettman et al [48] reported a significant relationship between age of implantation and speech perception.…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus that cochlear implants are largely safe across all age groups with congenital and acquired hearing loss, even for very young children ( Rajan et al, 2018 ; Uecker et al, 2019 ; Sharma et al, 2020 ; Deep et al, 2021 ; Naik et al, 2021 ; Purcell et al, 2021 ). The survival rates for cochlear implants are as follows [ Lane et al (2019) : 10-year cumulative survival rates 97.2%; Chen et al (2022) : 10-year rate 96.8%, 20-year rate 96.7%].…”
Section: Perspective: Cochlear Implant-specific Risks Can Be a Burden...mentioning
confidence: 99%
“…Numerous studies indicate that children and adolescents with congenital or early onset severe and profound hearing loss benefit from CI: it provides a clear benefit in the development of brain regions associated with hearing ( Sharma et al, 2002 ; Kral and Sharma, 2012 ; Kral et al, 2016 ; Cardon and Sharma, 2019 ; Lee et al, 2020 ; Wang et al, 2021 ) and supports auditory development ( Purcell et al, 2021 ) as well as the development of spoken language ( Percy-Smith et al, 2008 ; Peters et al, 2010 ; Geers et al, 2016 ). In particular, very early implantation ( Dettman et al, 2016 ; Ruben, 2018 ; Sharma et al, 2020 ; Naik et al, 2021 ) and bilateral implantations ( Lieu et al, 2020 ; Sharma et al, 2020 ) benefit the development of verbal language. For example, 64% of children who were implanted before the age of 12 months showed receptive and expressive language skills in the normative range at school entry ( Dettman et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It prevents children from enjoying satisfactory social lives and can contribute to poor mental health and social isolation. Delayed management of the problem may result in degeneration of the central auditory system, leading to missed opportunities for education,, employment, and a lower quality of life [ 1 , 2 ]. The prevalence of neonatal permanent sensorineural HL ranges from 0.1% to 0.6%, with an overall prevalence of 0.2% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cochlear implant has significantly improved the treatment outcome for many children with severe to deep hearing disability. The criteria for candidacy and age of the surgery was driven by technological advancement [ 2 , 6 ]. Parents of children with cochlear implant expect positive changes in language development, communication skills, academic progress, social life, and children’s future [ 7 ].…”
Section: Introductionmentioning
confidence: 99%